SISTEM TES MASUK MAHASISWA BARU BERBASIS WEBSITE DI UNIVERSITAS SAHID SURAKARTA - Agung Yusup Nugroho; Sri Huning Anwariningsih; Hardika Khusnuliawati (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2019)
Sahid University Surakarta is a private university and located at Jl. Adi Sucipto No.154, Jajar, Laweyan, Surakarta, Central Java. The test system for new student at Sahid Surakarta University is still very simple. The test for new students admission in 2018 at Sahid Surakarta University still used Google forms as a test medium. This study aims to design and implement a website-based new student test system at Sahid Surakarta University. System design methods based on OOAD (Object Oriented Analysis and Design). Data collection methods used observation, interviews, and literature review. The software development procedure used the waterfall model. While, the stages of development consist of needs analysis, design, coding, testing, and implementation. The research respondents are informatics engineering students of Sahid Surakarta University and third grade of high school students with 30 respondents. The results of this study are obtained: (1) the application website-based for new student admission test with randomization test method from the new to the old ones besides system reporting capabilities results of the exam and alsp analyze the results of the exam, (2)the application of test website-based for new student test runs 100”6 on test without errors in the aspects tested. In the aspect of testing based on user with the survey deployment method, the total value is 83.6” so the respondents strongly agree with the making of these systems and devices.